Moluscos del Ordovícico de la región de Trás-os-Montes (Zona Centroibérica, NE de Portugal) - Sá, Artur Abreu (Coloquios de Paleontología, 2009)
Ordovician molluscs collected from 34 fossil localities on the Trás-os-Montes region (Central Iberian Zone, northern Portugal) are here studied, following the recent detailed stratigraphic review of these materials inside a region with a previous scarce and poorly known paleontological record. The fossiliferous levels are located in the Marão, Moncorvo and Chão do Amieiral formations, ranging from middle Arenigian to middle Berounian in age (Floian to early Katian according to the Global Geochoronological Scale). From a taxonomic point of view, several bivalves (comprising the genera Modiolopsis, Babinka, Redonia, Cardiolaria, Praeleda, Ctenodonta? and Tancrediopsis), rostroconchs (Ribeiria, Tolmachovia, Technophorus), gastropods (Sinuites, Tropidodiscus, Holopea?) and cephalopods (endoceratoids and orthocerids) are described for the first time from the Trás -os-Montes region, including a review of Ordovician molluscs listed from early papers, through its original material stored in different Portuguese institutions. Our data allow to establish biostratigraphical correlation with other coeval mollusc associations known from reference sections placed in southern areas of the Portuguese Central Iberian Zone, like Valongo, Buçaco or Mação, as well with other Ordovician fossil localities in Spain and the Armorican Massif (west France). A recente revisão estratigráfica detalhada dos materiais do Ordovícico de Trás-os-Montes (Zona Centro-Ibérica, NE de Portugal), caracterizados por um escasso e pouco conhecido registo paleontológico, permitiu localizar um conjunto de 34 jazidas fossilíferas com restos de moluscos nos materiais das formações Marão, Moncorvo e Chão do Amieiral, dentro do intervalo temporal compreendido entre o Arenigiano médio e o Berouniano médio (Floiano a Katiano inferior da escala geocronológica global). Do ponto de vista taxonómico, descrevem-se pela primeira vez em Trás-os-Montes diversas formas de bivalves (géneros Modiolopsis, Babinka, Redonia, Cardiolaria, Praeleda, Ctenodonta? e Tancrediopsis), rostroconchas (géneros Ribeiria, Tolmachovia e Technophorus), gastrópodes (géneros Sinuites, Tropidodiscus e Holopea?) e cefalópodes (endoceratoídios e ortoceratídios, em nomenclatura aberta), tendo ainda sido revistas as escassas referências prévias de moluscos ordovícicos provenientes desta região, recorrendo ao material original depositado em distintas instituições portuguesas. Os resultados bioestratigráficos obtidos permitem establecer correlações com as asociações de moluscos conhecidas em sectores mais meridionais da Zona Centro-Ibérica portuguesa, como Valongo, Buçaco e Mação, bem como com jazidas do Ordovícico espanhol e armoricano.